Ex-Shaman: Threatened culture of the indigenous people Paiter Suruí and memory as resistance - De Souza, Diogo Matheus (2020)
This review presents the documentary-fiction Ex-Pajé (2018), directed by filmmaker Luiz Bolognesi, which addresses the recent history of the Paiter Suruí indigenous people, located on the border between the states of Mato Grosso and Rondônia (Brazil). The narrative develops from the point of view of Perpera Surui, a former shaman who was stripped of his post after the evangelical religion impacted Paiter Surui's traditional beliefs. Through a memory work and staging performed by the former shaman, friends and family, this documentary shows the impacts that the logging industry, agribusiness, and evangelical indoctrination have had on Paiter Suruí since the first contact with the whites, in 1969, to the present day. The focus is mainly on the cultural impacts caused by white people, ranging from the demonization of their religious practices to the search to erase their tradition and memory, transmitted orally in the intergenerational interaction. In a first visual comprehension, Ex-Pajé may lead the viewer to understand that in the portrayed context what remains are remains, residues of the culture and memory of the Paiter Suruí. However, such narrative can also be analyzed from the perspective of resistance, verifiable, among other evidences, in the work of memory by Paiter Suruí and in the creation of his enactments, which become a form of denunciation.